Genesis of the Yangjiakuang gold deposit, Jiaodong peninsula, China: Constraints from S-He-Ar-Pb isotopes, and Sm-Nd and U-Pb geochronology - Li, Jun-Jian; Dang, Zhi-Cai; Fu, Chao; Zhang, Peng-Peng; Tian, Jie-Peng; He, Jiang-Tao (Frontiers in Earth Science, 2023)
Located in the Penglai-Qixia-Fushan Gold Belt, the Yangjiakuang gold deposit formed in the marble of the Paleoproterozoic Fenzishan Group is different from the previous altered rock-type gold deposits whose host gold-bearing rocks are Archean gneiss and Mesozoic granite. Two gold orebodies have been explored within the Yangjiakuang gold deposit, and both of them were controlled by the Yangjiakuang syncline. Three ore-forming stages have been recognized, including the pyrite-sericite stage (I), the gold, polymetallic sulfide, and quartz stage (II), and quartz-calcite stage (III). The calcites, which represent the main metallogenic stage (II) at Yangjiakuang gold deposit, yielded a Sm-Nd isochron age of 123.5 ± 8.1 Ma (MSWD = 0.042). Subsequent geologic events were recorded by quartz diorite porphyrite dyke which are dated at 122.75 ± 0.66 Ma (MSWD = 1.5) by zircon LA-ICP-MS U-Pb dating. It is suggested that the gold mineralization took place in the early period of Early Cretaceous. The in-situ δ34S values of pyrites from two stages have a narrow range from + 5.65 to + 9.63‰ with an average value of 8.14‰, which indicate that the source of δ34S is related to the Guojialing granite and the Fenzishan Group. The lead isotopic compositions of pyrites (206Pb/204Pb = 16.615 to 16.832; 207Pb/204Pb = 15.275 to 15.403; 208Pb/204Pb = 36.829 to 37.470) show a consistent origin of the lower crust. The measured 3He/4He (40Ar/36Ar) of hydrothermal fluids in pyrites are 0.641 to 1.132 Ra (637.5 to 1162.7), indicating that the ore-forming fluid originating from a mixing of crustal and mantle components. It is suggested that the gold mineralization is associated with extensional tectonic inversion caused by the rollback of the subducting Izanagi Plate during the early Cretaceous, which triggered partial melting of mantle and lower crust, and subsequent magma mixing and exsolution of ore-bearing fluids. These fluids extracted ore-forming materials from the enclosing rocks of the Jiaodong Group, the Fenzishan Group, and the Guojialing granite to form the ore-forming fluids.